Comparison of detection percentage and morphology of myocardial bridge between conventional coronary angiography and coronary CT angiography - Seyed Hassan Eftekhar-Vaghefi; Somayeh Pourhoseini; Maryam Movahedi; Shohre Hooshmand; Mohammad Ali Ostovan; Pooyan Dehghani; Nikan Ostovan (Journal of Cardiovascular and Thoracic Research, 2019)
Introduction: Myocardial bridge (MB) is a congenital anomaly in which a segment of a coronary artery is surrounded by myocardium. In our study, we want to use conventional coronary angiography (CCA) to describe morphologic characteristics of MB (unidentified or identified) in the patients with documented evidence of MB in coronary computed tomography angiography (CCTA). Methods: The present study was designed as cross-sectional and was conducted on 47 patients with documented evidence of MB in CCTA, who were referred to Nemazee and Faghihi hospitals for performing coronary angiography during a one year period. We compared the morphologic characteristics of tunneled segments, which were missed at CCA (unidentified), and the tunneled segments which were identified with CCA. Results: In sum, MB was found in 16 (34%) patients at CCA (identified), and it was not found in 31 (66%) patients (unidentified) based on compression sign. No significant correlation was found between the percentage of systolic compression and the length and depth of the tunneled segment in identified group (r=0.73, P = 0.18; r=1.09, P = 0.15; respectively). Degree of atherosclerotic plaque formation (diameter stenosis, percentage) (mean, 0.25 (25%) ±0.29; range, 0-0.98) of the tunneled segments in unidentified group was significantly more than the same degree (mean, 0.07 (7%) ±0.13; range, 0-0.41) of the identified group (P = 0.03). The measurement of the trapezoid area under the tunneled segment with this formula [(MB length+ intramyocardial segment) ×depth/2] had significant relation with systolic compression (r=0.304, P = 0.03) and defined the cut-off value of 250 mm2 as the value of significant difference in detecting myocardial bridging with CCA. Conclusion: Our results showed that in most of identified MBs in CCA the tunneled segment area was equal and more than 250 mm2. In addition, the degree of atherosclerotic plaque of the tunneled segments at CCA was significantly more in unidentified group.